1997
DOI: 10.1038/bjc.1997.540
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lobular carcinoma of the breast has better short- and long-term survival than invasive ductal carcinoma

Abstract: Invasive lobular carcinoma of the breast has better short-and long-term survival than invasive ductal carcinoma S Toikkanen', L Pylkkanen2and H Joensuu3Departments of 'Pathology and 2Oncology, University Central Hospital of Turku, Kiinamyllynkatu 10, FIN-20520 Turku, Finland; 3Department of Oncology, University Central Hospital of Helsinki, Haartmaninkatu 4, Helsinki, Finland Summary The outcome and prognostic factors of 217 women with invasive lobular carcinoma (ILC) and those of 1121 women with invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
1
8

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 20 publications
2
107
1
8
Order By: Relevance
“…The morphology categories special type and comedocarcinoma were associated with lower RERs of death than infiltracting ductal carcinoma (Table 5). The special type category includes, tubular, mucinous and papillary histotypes, which were reported to have good prognoses in a previous population-based study (Li et al, 2003), and in other studies (Cooper et al, 1978;Fisher et al, 1980;Wargotz and Silverberg, 1988;Ellis et al, 1992;Silverstein et al, 1994;Pedersen et al, 1995;Reinfuss et al, 1995;Toikkanen et al, 1997;Diab et al, 1999). Comedocarcinoma also had a relatively good prognosis in a previous study (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…The morphology categories special type and comedocarcinoma were associated with lower RERs of death than infiltracting ductal carcinoma (Table 5). The special type category includes, tubular, mucinous and papillary histotypes, which were reported to have good prognoses in a previous population-based study (Li et al, 2003), and in other studies (Cooper et al, 1978;Fisher et al, 1980;Wargotz and Silverberg, 1988;Ellis et al, 1992;Silverstein et al, 1994;Pedersen et al, 1995;Reinfuss et al, 1995;Toikkanen et al, 1997;Diab et al, 1999). Comedocarcinoma also had a relatively good prognosis in a previous study (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…This result may in part be explained by the histology of lobular carcinoma, which is characterized by abundant fibrous tissue, that is diffusely infiltrated by uniform, small round cells, which typically exhibit lower mitotic activities than invasive ductal carcinomas, and the lower securin expression that we observed, may simply reflect lower tumor proliferative rates. [26][27][28] A further explanation for the comparatively lower securin expression seen in lobular carcinomas compared to ductal carcinomas was that two-thirds of the lobular carcinomas exhibited a low degree of nuclear pleomorphism and only one tumor was markedly pleomorphic.…”
Section: Securin Overexpression In Breast Cancermentioning
confidence: 99%
“…In addition, it has been reported that ILC is less responsive to chemotherapy [3,21], lacks potential benefit of HER2 targeted therapy [16,17], being typically HER2 negative, but is more often HR positive and responsive to adjuvant hormonal therapy (HT) [11,22,23]. Reported prognosis of ILC varies and has been reported to be worse [1,9,[24][25][26][27], no different [17,[28][29][30][31][32], or better [6] than that with IDC.…”
Section: Introductionmentioning
confidence: 99%